Application of Leiper's tourist attraction system to small-scale sport event tourism in Malaysia - Yusof, Aminuddin; Mohd Shah, Parilah; Soh, Kim Geok (IDOSI Publications, 2012)
There is a lack of literature on sport tourists attending small-scale sport events and their travel behaviors in Malaysia. This lack of data makes it difficult for tourism authorities in to implement effective market segmentation and targeting. Thus it is necessary to conduct a study to explore the potential of small-scale sporting event as tourist attraction in Malaysia using Leiper’s (1990) tourist attraction system as framework. A study is conducted on participants and spectators attending a mountain bike race and motor cross events in Lake Kenyir Malaysia. Data were collected quantitatively from 400 subjects using the Leisure Motivation Scale developed by Ragheb and Beard (1983). Data were analyzed using descriptive statistics and logistic regression. Visitors to sport event at Lake Kenyir fall into three categories: (1) sport excursionist, (2) active sport tourist and (3) passive sport tourists and the majority of the respondents (81.75%) were sport tourists. The results indicate factors such as competence mastery and intellectual factors are significant variables which motivate people to seek active sport-oriented vacations. Passive sport tourists are motivated by social factors and the need to escape from over stimulating situations. This study confirmed the usefulness of Leiper’s tourist attraction theory in sport tourism.